2020
DOI: 10.1038/s41598-020-67411-w
|View full text |Cite|
|
Sign up to set email alerts
|

GL261 luciferase-expressing cells elicit an anti-tumor immune response: an evaluation of murine glioma models

Abstract: Preclinical models that reliably recapitulate the immunosuppressive properties of human gliomas are essential to assess immune-based therapies. GL261 murine glioma cells are widely used as a syngeneic animal model of glioma, however, it has become common practice to transfect these cells with luciferase for fluorescent tumor tracking. The aim of this study was to compare the survival of mice injected with fluorescent or non-fluorescent GL261 cells and characterize the differences in their tumor microenvironmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
5
28
0
Order By: Relevance
“… 90 However, a more recent study by Sanchez et al highlighted improved survival in mice injected with GL261 tumors expressing luciferase with or without an additional fluorescent protein marker, relative to wild-type tumor cells. 91 They also showed increased inflammatory immune cells in tumors expressing luciferase and a fluorescent protein marker as well as increased secretion of inflammatory cytokines by these cells. 91 Given the mixed literature on the subject, attention should be paid to the use of luciferase or other nonendogenous tumor tracking proteins, such as GFP, especially if investigating immunotherapies.…”
Section: Syngeneic Murine Models Of Gbmmentioning
confidence: 96%
“… 90 However, a more recent study by Sanchez et al highlighted improved survival in mice injected with GL261 tumors expressing luciferase with or without an additional fluorescent protein marker, relative to wild-type tumor cells. 91 They also showed increased inflammatory immune cells in tumors expressing luciferase and a fluorescent protein marker as well as increased secretion of inflammatory cytokines by these cells. 91 Given the mixed literature on the subject, attention should be paid to the use of luciferase or other nonendogenous tumor tracking proteins, such as GFP, especially if investigating immunotherapies.…”
Section: Syngeneic Murine Models Of Gbmmentioning
confidence: 96%
“…Just as increased knowledge about the mutational burden of GL261 tumors has led increasingly to them being viewed as a model of hypermutated glioblastoma, 26 , 82 increased knowledge of other experimental variables should change our practices moving forward. For instance, knowing that modification of the GL261 cell line with bioluminescent reporters enhances its antigenicity 52 should temper the enthusiasm of successful immunotherapeutic strategies vetted in that model and perhaps encourage the utilization of a second model system like CT-2A, SB28, or wild-type GL261 for verification. Other sets of experimental factors should inform our practices as well.…”
Section: Discussionmentioning
confidence: 99%
“…While an older study failed to observe any gross changes in overall growth kinetics or T-cell infiltration between GL261 and GL261-Luc tumors, 51 a more recent study found that wild-type GL261-bearing mice had shorter survival than mice bearing either of 2 types of Luciferase-expressing GL261. 52 The ability of each of these 3 cell lines to replicate in vitro was comparable and the difference in survival was instead linked to a more inflammatory state within the Luciferase-expressing tumors as shown by a cytokine microarray revealing elevated IFN-y and IL-1α levels. 52 Whether the differential cytokine levels in the tumor microenvironment are sufficient to dictate a differential response to anti-PD-1 therapy is yet unknown, but the equivalence of GL261 and GL261-Luciferase cell lines should not be taken for granted without further study.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reports that the implantation of adult mice with cells expressing luciferase may elicit an increased pro-inflammatory immune response, when compared with the implantation of Wild type glioma cells ( Sanchez et al., 2020 ). In this study, luciferase expressing cells were implanted in adult animals, which have a fully developed immune system.…”
Section: Limitationsmentioning
confidence: 99%